2012
DOI: 10.1089/jwh.2012.3650
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Symptoms and Care Delivery for Chronic Obstructive Pulmonary Disease

Abstract: Background: Morbidity and mortality for women with chronic obstructive pulmonary disease (COPD) are increasing, and little is known about gender differences in perception of COPD care. Methods: Surveys were administered to a convenience sample of COPD patients to evaluate perceptions about symptoms, barriers to care, and sources of information about COPD. Results: Data on 295 female and 273 male participants were analyzed. With similar frequencies, women and men reported dyspnea and rated their health as poor/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 36 publications
3
44
2
1
Order By: Relevance
“…Although women have earlier been found to have a longer diagnostic delay and increased difficulties of reaching a physician,21 there are no consistent findings of gender differences in treatments in the earlier studies,22 as we found in the present study. An explanation of the gender differences could be an inherent difference in the appreciation of, for example, rehabilitation efforts.…”
Section: Discussioncontrasting
confidence: 91%
“…Although women have earlier been found to have a longer diagnostic delay and increased difficulties of reaching a physician,21 there are no consistent findings of gender differences in treatments in the earlier studies,22 as we found in the present study. An explanation of the gender differences could be an inherent difference in the appreciation of, for example, rehabilitation efforts.…”
Section: Discussioncontrasting
confidence: 91%
“…Spirometry testing and referral to a pulmonologist are less common for women [4,14,15]. Women reportedly suffer a delay in the diagnosis of COPD, explainable in part by voluntary postponement of access to a consultation or in some patients by the prevalence of symptoms of fatigue or depression that point to a different type of treatment [16]. Allowing for these reservations, the prevalence of COPD is currently estimated, depending on the country, to range from 4.5% to 10.2% [17,18].…”
Section: Epidemiology Of Copd In Womenmentioning
confidence: 99%
“…In addition, people who speak a language other than English face significant barriers in access to care and in receiving quality health care (3, 4, 15, 16, 19, 23, 24, 26, 30-34, 50, 54, 86). Health outcomes and care received also vary between men and women (5,18,20,43,51,57,62,75,93,98,102). Finally, people with disabilities frequently cannot access the benefits, services, and information provided by health care systems to the same extent as those without disabilities (29,46,53,55,77,92,95).…”
Section: Introductionmentioning
confidence: 99%